Erythroid progenitor cell–mediated spleen–tumor interaction deteriorates cancer immunity - Zhi-Zhong Wu; Wei-Wei Deng; Su-Wen Zhu; Wen-Da Wang; Shuo Wang; Qi-Chao Yang; Hao Li; Liang Mao; WanJun Chen; Zhi-Jun Sun (Proceedings of the National Academy of Sciences, 2025)
Understanding both local and systemic immunity is essential to optimizing the effectiveness of immunotherapy. However, the dynamic alterations in systemic immunity during tumor development are yet to be clearly defined. Here, we identified a previously unrecognized connection that bridges the interaction between the spleen and tumor through erythroid progenitor cells (EPCs), which suppress tumor immunity and promote tumor progression. We performed the single-cell RNA-seq and RNA-seq to demonstrate the presence of EPCs and identify the characteristic and an immunomodulatory role of EPCs during tumor progression. These tumor-hijacked EPCs proliferate in situ in spleens and impaired systemic and local antitumor response through the interaction between tumor and spleen. Specifically, the splenic CD45 − EPCs secreted heparin-binding growth factor to regulate PD-L1-mediated immunosuppression of splenic CD45 + EPCs. Educated CD45 + EPCs from the spleen then migrated to the tumors via the CCL5/CCR5 axis, thereby weakening local antitumor immunity. Consequently, targeting EPCs not only revitalized antitumor immunity but also improved the anti-PD-L1 effect by promoting intratumoral T cell infiltration. Importantly, CD45 + EPCs are associated with immunosuppression and reduced survival in patients with head and neck squamous cell carcinoma. Collectively, these findings reveal the role of EPCs in orchestrating the interaction between the spleen and tumor, which could have significant implications for the development of more effective cancer immunotherapy.